(untitled) (Journal of actual problems of jurisprudence, 2020)
This article explores the scientific approaches to the concept of “land development”, which is important for the forced withdrawal of land. The authors note that at present there is no uniform understanding of this concept, which gives rise in practice to a large number of land disputes, the lack of unified approaches in law enforcement practice, which causes dissatisfaction of land owners and land users. The theoretical significance of the study is that it develops and gives new impulses to the legal Institute “Termination of rights to land plots and other rights to land” of a Special part of the land law of the Republic of Kazakhstan, complements the theory of land law, promotes the development of interest in the issues under consideration by new researchers, scientists, students and other interested persons. The results of this study will help to establish a uniform practice in the withdrawal of land from the owner and the right of land use from the land user in connection with the non-development of land plots. The article provides a review and comparative analysis of the legislation of foreign countries, a theoretical analysis of various scientific points of view and approaches, an analysis of law enforcement practice, which made it possible to formulate the author’s definition of the concept of “land development” and offer practical recommendations for improving the land legislation of the Republic of Kazakhstan. Key words: land, ownership and other rights to land, expropriation of land, land development, compensation.